Проектирование легких самолетов - Бадягин Александр Алексеевич (Машиностроение, 1978)
Экземпляры: КХ (20120806) / Инвентарный номер: 694630 / Цена: 0.80 / Сис.шифр: 629.13 / Авт.знак: Б 15 / ГРНТИ: 73 / ББК: 39